2018
DOI: 10.1111/cns.13063
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture as a multifunctional neuroprotective therapy ameliorates cognitive impairment in a rat model of vascular dementia: A quantitative iTRAQ proteomics study

Abstract: Aims: Acupuncture has been reported to affect vascular dementia through a variety of molecular mechanisms. An isobaric tag for relative and absolute quantification (iTRAQ) with high-resolution liquid chromatography-tandem mass spectrometry (LC-MS/MS) analyses makes it possible to attain a global profile of proteins. Hence, we used an iTRAQ-LC-MS/MS strategy to unravel the underlying mechanism of acupuncture.Methods: Wistar rats were subjected to vascular dementia with bilateral common carotid occlusion. Acupun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(63 citation statements)
references
References 40 publications
1
61
0
1
Order By: Relevance
“…Vascular cognitive impairment (VCI) is termed as a spectrum of cognitive dysfunction associated with vascular disease origins from mild cognitive impairment to dementia . White matter damage due to chronic cerebral hypoperfusion is involved in a variety of neurological disorders including VCI .…”
Section: Introductionmentioning
confidence: 99%
“…Vascular cognitive impairment (VCI) is termed as a spectrum of cognitive dysfunction associated with vascular disease origins from mild cognitive impairment to dementia . White matter damage due to chronic cerebral hypoperfusion is involved in a variety of neurological disorders including VCI .…”
Section: Introductionmentioning
confidence: 99%
“…By using a proteomics approach, researchers found that acupuncture can induce a cluster of proteins related to oxidative stress and reduced ROS production in a rat vascular dementia model. The same study also reported decreased neuronal apoptosis and improved LTP and cell survival in the acupuncture group, suggesting the multitargeted effect of the intervention [55]. Similarly, in a study conducted by Han and colleagues, EA was found to effectively improve cognition in mice injected with lipopolysaccharide, which is widely used to induce inflammation.…”
Section: Reduction Of Oxidative Stressmentioning
confidence: 67%
“…The mechanism through which acupuncture modulates the redox pathways and reduces oxidative stress remains unclear. Acupuncture likely affects a cluster of oxidative stress-related enzymes, inducing a nonspecific response [54,55]. By using a proteomics approach, researchers found that acupuncture can induce a cluster of proteins related to oxidative stress and reduced ROS production in a rat vascular dementia model.…”
Section: Reduction Of Oxidative Stressmentioning
confidence: 99%
“…Rat VD model (Chen et al 2015;Jia et al 2015;Yang et al 2018) was used in the study, briefly, rats were anaesthetised by intraperitoneal injection of 10% chloral hydrate (350 mg/kg) and placed on an alcohol-sterilized surgical plate. The bilateral common carotid arteries were separated from the vagus nerve and ligated with a 4-0 surgical suture.…”
Section: Preparation Of the Vd Model Vdmentioning
confidence: 99%